2009
DOI: 10.1111/j.1759-3441.2009.00003.x
|View full text |Cite
|
Sign up to set email alerts
|

The Boom We Didn’t Really Have: Australian Economics Degree Enrolments, 1990–2007*

Abstract: This paper revisits the matter of attracting students to study economics, an issue that faces every Australian university economics department. While the Australian economy has been in a boom phase for some period it has not led to a relative increase in economic degree enrolments for local universities. While some of the Go8 universities have seen a steady increase in economics degree enrolments between 1995 and 2007, the national picture, taken over a longer period, reveals that economic degree enrolments as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…Also, as enrolments in economics did not follow the increase in total student enrolments over the 2001–2007 period, the share of economics enrolments fell from 1.20 per cent in 2001 to 1.13 per cent in 2007. These results are very close to those of Millmow () that indicate that economics has steadily lost share in the Australian tertiary education market.…”
Section: Literature Reviewsupporting
confidence: 88%
“…Also, as enrolments in economics did not follow the increase in total student enrolments over the 2001–2007 period, the share of economics enrolments fell from 1.20 per cent in 2001 to 1.13 per cent in 2007. These results are very close to those of Millmow () that indicate that economics has steadily lost share in the Australian tertiary education market.…”
Section: Literature Reviewsupporting
confidence: 88%
“…One does not have to draw a long bow to connect these concerns about the type of economic coursework on offer with the decline in relative popularity of economic courses over several decades (Millmow, , , ; Round and Shanahan, ), despite some evidence of a slight reversal in the share of economics enrolments from 2007 to 2010 (Millmow, ). Millmow () found that enrolments in an economics major relative to total enrolments in all undergraduate degrees fell from 1.85% for 1990–1992 to 1.21% for 2005–2007. The number of Australian university economics departments dropped from 37 in 2000 to 27 in 2009 (Millmow, ).…”
Section: The Case For Curriculum Renewal Through Learning Standardsmentioning
confidence: 99%
“…Millmow () found that enrolments in an economics major relative to total enrolments in all undergraduate degrees fell from 1.85% for 1990–1992 to 1.21% for 2005–2007. The number of Australian university economics departments dropped from 37 in 2000 to 27 in 2009 (Millmow, ). Students seem to have been drawn to alternative business disciplines in part because of dissatisfaction with pedagogy in economics.…”
Section: The Case For Curriculum Renewal Through Learning Standardsmentioning
confidence: 99%
“…He also found that seven universities did not even offer an economics major in their business degree. In what was the latest survey on the matter Round and Shanahan (2010) agreed with Millmow (2009) that over an eighteen‐year period, economics has steadily lost market share in the Australian tertiary market, although the rate of decline has not been nearly as severe in the noughties as it was in the 1990s, and that, in the last few years, there has been a small increase in economics degree enrolments.…”
Section: Introductionmentioning
confidence: 99%
“…It would be interesting to see if the academic economics profession will soon see an increase in the size of their classes. An earlier account (Millmow, 2009) showed that the Australian economic profession had missed out on the boom in terms of attracting more student enrolments both absolutely and as a percentage of total student enrolments. That paper further uncovered that while the GO eight universities have seen a steady increase in economics degree enrolments between 1995 and 2007, the national picture, taken over a longer period reveals that economic degree enrolments as a percentage of the overall student population fell.…”
Section: Introductionmentioning
confidence: 99%